(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
The article discusses the various terms used to define the name of the commercial associations of people. Attention is focused on the analysis of structural and semantic features of firmonims of Kriviy Rih, patterns of their occurrence and functioning in the urbanonimic space. The most important conditions for a successful firmonim are determined.